Diagnóstico de problemas de fertilidad de suelos: visión actual - Flor Montoya, Carlos A. (International Center for Tropical Agriculture, 2010)
Diagnosis of soil fertility problems: Current vision The importance of a ‘correct diagnosis’ of soil fertility and other problems faced by the rice crop as the basis of a ‘correct treatment’ is reviewed and highlighted. The diagnosis of nutritional disorders of rice crops indicates that there are common aspects and weaknesses in both upland and irrigated (flooded) crops. In the case of irrigated rice, any situation of nutrient deficiency or plant toxicity due to a given nutrient is affected by the reductive reactions that nutrients undergo in the absence of oxygen; these reactions are typical of the chemistry of flooded soils. The different stages of diagnosis—clinic, preliminary, advanced, and final—are described and analyzed. Guidelines are also provided for visually characterizing symptoms of nutritional disorders and it is suggested to prepare symptomatology tables that contain the highest number possible of nutritional disorders. These tables can be used to replace the classical representation of symptoms, which generally consists of one rice leaf with a single manifestation of the disorder, and to characterize double and triple deficiencies as well as combined deficiencies and toxic effects.